(untitled) (Linguistics in Amsterdam, 2017)
In an attempt to begin to establish the productive knowledge of morpho-syntax (of Dutch), shared by all adult native speakers, this study examined the extent to which several patterns of Dutch syntax are present in the speech of 98 adult native speakers of Dutch, differing in age (18–76) and level of education and profession (EP-Low vs. EP-High), who performed four speaking tasks, differing in formality (formal vs. informal) and discourse type (descriptive v. argumentative). The size of the corpus is 12 hours (80,000 plus word tokens). The study was guided by the following question, derived from Hulstijn’s (2015) theory of Basic Language Cognition: Which syntactic patterns (of the ones under examination) are acquired (in all likelihood) by all native speakers? Most of the patterns under investigation were chosen from the perspective of Hawkins’ (2004, 2014) efficiency theory. The findings suggest that adult native speakers of Dutch produce subordinate-clause patterns, such as complement clauses, adverbial clauses and relative clauses at their base position in the matrix clause (to the right of the verb, NP, etc.), but that the phenomenon of clause fronting is common only with respect to some adverbial clause types, such as conditional clauses beginning with als (‘if’). Verb clusters with modal auxiliaries and the passive voice also appear to belong to shared grammatical knowledge. In contrast, the findings suggest that it-cleft sentences, wh-cleft sentences, the fronting of conjunction-less conditional clauses, fronting of infinitival clauses, and center-embedding a clause within another clause may not belong to shared grammatical cognition. The findings are claimed to be potentially relevant to any theory of language acquisition aiming to explain the following two questions: (i) Why it is that some syntactic patterns are not and other patterns are acquired by all native speakers? and (ii) How can the acquisition of these shared patterns be accounted for in terms of learning mechanisms (nature) and exposure (nurture)?